Lagomorphs and paleoenvironment of the Taatsyn gol (Valley of Lakes), Early Miocene, Mongolia - Baatarjav, Bayarmaa (Mongolian Journal of Paleontology, 2024)
Lagomorpha is one of the most abundant and species-rich small mammal groups recovered from Oligocene and Early Miocene fossil localities of Mongolia. However 4 genera and 9 species were identified from the boundary of Late Oligocene and Early Miocene. The general trend in the evolution of ochotonids was towards the complete disappearance of roots, the development of hypsodonty and the increase in the masticatory surface of cheek teeth, which was an adaptation to feeding on harsh vegetation, cropping plants and grinding them. The development of more complicated morphology of the occlusal surface can be traced in the teeth of both Alloptox and Bellatona. Favorable landscape and climatic conditions led to wide adaptive radiation of ochotonids in Asia. Монгол орны түрүү миоцены туулай хэлбэртэн (Lagomorpha) багийн амьтдын судалгаа, эртний орчин (Нууруудын хөндий, Таацын гол)